Novel star-shaped fractal antenna for multiband applications. Issue 10 (23rd November 2015) - Rao, Neeraj; Malik, Ankit; Kumar, Rahul; Goel, Shobhit; Kumar V, Dinesh
Abstract : Fractals have unique properties such as self-similarity and space-filling. The use of fractal geometry in antenna design provides a good method for achieving the desired miniaturization, multi-band, and wideband properties. In this communication, novel fractal geometry is proposed based on which a multiband antenna is designed. The proposed antenna has fractal patches which are shaped as different iterations of an eight- pointed star. The multiband behavior is in the frequency range from 4.50 to 17.00 GHz. The proposed antenna is designed on a dielectric substrate Roggers RO4003 lossy with a dielectric constant of εr = 3.55. The antenna has applications in commercial and military communication system.